The Character Education Meaning on Rites before Wedding Party in Muna Ethnic of Southeast Sulawesi - Hafsah, Wa Ode Sitti (International Research Journal of Management, IT & Social Sciences, 2017)
The local culture is an important issue to be investigated since it gives much interesting process and great values. Before wedding party, there are several rites that must be done by Muna ethnic. They are feenaghoo tingguno karete, kafeena, and karompua. Feenaghoo tingguno karete is a delegation of manâs parents visits the womanâs house to ask about the status of woman. Kafeena is manâs parents delegate their relatives to bring something to womanâs house. Last, karompua is meeting of both families to discuss the time and procedures of the marriage settlement. Data of this study collected through observation and interview and analyzed based on descriptive qualitative approach. The result of this study shows that three rites have several character education meanings as follow: (1) careful; both man and woman evaluate each other before deciding to get marriage; (2) respectiveness; both families respect each other; (3) togetherness; both families help each other in holding wedding party as one family and eating together; (4) social norm; manâs family always gives something before visiting the womanâs house and the womanâs family also welcome the manâs family attendance with various dish services, and (5) philosophy meaning; in those rites conveyed several Munaâs philosophical principles.